A crítica à indústria cultural segundo Theodor W. Adorno - Oscar Palma Lima (2002)
The following dissertation investigates the thought of Theodor W. Adorno on the concept of culture industry. It reconstruct the pathway of the Adornian rellection, since the debate happened along the thirties with Waller Benjamin, when both authors were developing a philosophical theory about the art's condition at the early twentieth century capitalist societies. Ahead, it inquires how Adorno, jointly with Max Horkheimer, elaborate in the Dialectic of Enlightenment a meta-theory of the instrumental rationality and the impact of this work in his philosophical writings. The centrality of the thought concerning the culture industry in the work of Adorno is analyzed, at last, in the several essays where the author theorizes about the consequence range of the commodified culture to the notions of critique, language and philosophical reflection.